Online Islamic Education Platforms, Islamic Reformism and Transmission of Islamic Knowledge in CIS Countries - Yarosh, Oleg (Journal of Muslims in Europe, 2026)
Despite the increasing presence of Islamic digital learning in the education landscape of the Commonwealth of Independent States (CIS) region, it has largely been ignored in research. This article aims to highlight Online Islamic Education Platforms (OIEPs) by examining their role in spreading Islamic knowledge in CIS countries. It discusses several OIEPs within the broader context of Islamic education in the region and the global expansion of OIEPs. By analysing the web content and curriculum ideologies of OIEPs I suggest that regional OIEPs tend to reflect locally accepted religious orthodoxies. In contrast, trans-regional OIEPs, which operate outside state-controlled Islamic environments, are more aligned with global trends, whether that involves inter-madhhab Sunnism, Salafism or Islamic reformism. Islamic reformism, which is the primary focus of the article, aims to bridge the gap between religious and secular disciplines, particularly social sciences and humanities, and to promote Islamic education reform in the region.